KEBIJAKAN MONETER DAN PENGARUHNYA TERHADAP PEREKONOMIAN INDONESIA SECARA GLOBAL - seno sudarmono Hadi (Universitas Bina Sarana Informatika, 2017)
Abstract – Indonesia's economic growth is so rapid at the end of this end result in the inflation rate. As happened in the last six years was recorded inflation increases quite dramatically from the year 2009 of 2.78 to 5.50 in the year 2014, despite declines in terjad flktuasi rising inflation. Inflation is the impact of terjadnya increase perekonmian growing on a country by increasing the economic growth of trading activities or buying and selling increased as the supply increases of businesses or producers resulting in an increase of more than buyers or consumers to shop, resulting in price increases of some good product ata goods market services. One way to anticipate the growing inflationary policy, the government is supposed to do parties with Binga rate policy in this regard should be made the monetary authorities in Indonesia, Bank Indonesia. With interest rate policy is expected minimal rate of inflation can be prevented to a lower level so that people can enjoy the products at a more affordable price so that the prosperity of the people can be achieved. Keywords: Interest Rates, Inflation, Economic Growth